Agronomic management systems for rehabilitation and sustained crop production in coastal agro ecosystem of Tamil Nadu, India - R. Immanuel; M. Thiruppathi; V. Mullaivendhan (Innovations in Agriculture)
Field experiments were conducted in the degraded coastal agro ecosystem with different land management methods and ameliorative amendments such as to boost the growth of identified MPT’s in degraded soil. The field experiment were laid out in split plot design and consisted of 16 treatment combinations with four land management treatment in the main plots (M1-pit method, M2-trench method , M3-mound method and M4-Auger hole method) and four ameliorative treatment in sub plots (S1-FYM @ 12.5 t ha-1 + Gypsum @ 200 kg ha-1+ ZnsO4 @ 25 kg ha-1 + Azospirillum @ 2kg ha-1+ Phosphobacteria @ 2 kg ha-1, S2- Pressmud @ 15 t ha-1+ Gypsum @ 200 kg ha-1+ ZnsO4 @ 25 kg ha-1+ Azospirillum @ 2kg ha-1 + Phosphobacteria @ 2 kg ha-1, S3– Composted coir pith @ 10 t ha-1 + Gypsum @ 200 kg ha-1 + ZnsO4 @ 25 kg ha-1 + Azospirillum @ 2 kg ha-1+Phosphobacteria @ 2 kg ha-1 and S4- no amendments). The treatment was replicated three times for the identified MPT’s of Pongamia pinnata Based on the results of present study it can be clearly found that trench method of planting in combination with FYM @ 12.5 t ha-1, Gypsum @ 200 kg ha-1, ZnsO4 @ 25 kg ha-1, Azospirillum @ 2 kg ha-1 and phosphobacteria @ 2 kg ha-1 recorded the highest establishment percentage height, girth, PGR and taproot length of identified MPT’s of Pongamia pinnata n the degraded coastal soil.